(untitled) - Canter, Larry W. (America, 1985)
This book is organized into five chapters and 16 appendices. Following an introductory chapter which focuses on summary information from 434 included references, chapters 2 through 4 are related to environmental impact studies for dam and reservoir projects, channelization projects, and dredging projects, respectively.
Keywords: Hydraulic engineering; Environmental aspects